PATHOLOGICAL AND DIAGNOSTIC PECULIAR OF PANCREATIC DUCTAL ADENOCARCINOMA ON MULTIPHASE CT (The Research of Medical Science Review, 2025)
Objective Of Study: Pancreatic ductal adenocarcinoma (PDAC) presents itself in different phases of CT imaging, aiming to distinguish it from other pancreatic conditions. Multiphase CT scans can identify and determine the extent of PDAC, contributing to more effective treatment planning Research Design: The research design for the proposed study was a prospective cross-sectional study. Place & Duration of Study: The research will be conducted at Allied Hospital, Faisalabad. From July 2024 to December 2024. Material & Methods: This descriptive cross-sectional study was conducted in the radiology department of Islamabad Diagnostic Center, Faisalabad from July 2024 to December 2024. A sample of total of 50 participant from which 50% were male and 50% were femaleselected. These all of the patients who meet our criterion were directed to the radiology department for Multiphase CT pancreatic protocol on 64 slices CT scan. CT images of the prostate of different phases were used for PDAC diagnosis. Independent radiologists examine the images of these patients. The Frequency, percentage, and correlation of patient data were evaluated by the SPSS 21.0 version. Results: Pancreatic head was the site of the tumor in the majority of the tumours (100%), the vast majority of tumours (50%) involved vascular encasement, up to 25% of cases had metastases. Although the venous and delayed phases improved the evaluation of lymph nodes and metastatic dissemination, the arterial phase was more effective in identifying hypoattenuating lesions. The diagnostic test achieved 87% sensitivity in reporting genuine cases and displayed 82% specificity in correctly identifying healthy patients. Tumor visibility varied significantly between CT phases, according to statistical analysis (p = 0.0003). Conclusion: Multiphase CT has an excellent diagnostic accuracy and is vital for complete evaluation of PDAC, allowing for the support of treatment planning. This has clinical utility, which includes its ability to demarcate tumor margins, its intermediate ability to assess vascular invasion, its capacity to identify metastases, and the higher utility of its nonsentinel nodes for surveillance. However, due to the difficulty in distinguishing PDAC from benign disease, EUS or MRI is added.